Identification of Anorganic Waste in Sebalang Beach and Tanjung Selaki Beach, Tarahan Village, Subdistrict Katibung, Lampung Selatan District - Wardana, Jaya; Maharani, Henni Wijayanti; Diantari, Rara (Faculty of Fisheries and Marine, Universitas Riau, 2022)
The increase in the human population causes the amount of organic and inorganic waste to increase. The decomposition of inorganic waste is relatively longer compared to organic waste, therefore it is very harmful to the coastal environment. The purpose of this study was to determine the type, weight, distribution, density, and to compare the density and type of inorganic waste at Sebalang Beach and Tanjung Selaki Beach. Garbage collection and measurement of oceanographic parameters were carried out directly from March to April 2020. Garbage was collected on a 100 meter transect following the shoreline at each point at high tide and low tide. Current and wave were measured at two points with four repetitions. Waste data is separated by type, weight and presented descriptively. The results showed that the amount of macro-debris waste was higher than meso-debris waste with plastic waste that was more dominant than other types of waste. Sebalang Beach has a higher density of trash than Tanjung Selaki Beach.